Nutrition Assessment and Support in Children With End‐Stage Liver Disease. (6th March 2013) - Young, Sona; Kwarta, Elizabeth; Azzam, Ruba; Sentongo, Timothy
Abstract : Malnutrition is a treatable complication in children with end‐stage liver disease (ESLD). Biliary atresia and other cholestatic disorders are the most frequent cause of ESLD in children. No single variable provides adequate information about nutrition status, yet effective nutrition support is the one intervention known to improve pre‐ and posttransplant outcomes. A proactive approach consisting of screening anthropometry interpreted using appropriate growth references, recognition of clinical manifestations associated with micronutrient deficiency, and timely aggressive nutrition support is of a paramount importance to maximize anabolism and optimize outcomes. This article presents the principles of nutrition assessment, intervention, and monitoring in children with ESLD.